Evaluation of Water Resources Carrying Capacity in the Upper Reaches of Hanjiang River Based on Quantity and Mass Flow - Gan, Longyan (International Journal of Natural Resources and Environmental Studies, 2025)
Water resources is one of the important resources of human society In order to scientifically analyze and promote sustainable development, it is necessary to build a comprehensive evaluation system of multiple elements of water resources carrying capacity. Therefore, based on the four dimensions of quantity, quality and flow of water resources, it is constructed by target layer, dimension layer This paper mainly uses analytic hierarchy process, AHP model and TOPSIS evaluation model to evaluate the current situation of water resources carrying capacity in Hanjiang River Basin, so as to provide theoretical support and foundation for ecological construction and urban development in the upper reaches of Hanjiang River, The evaluation results are as follows: ① the AHP model and TOPSIS evaluation model used in this paper can clarify the water resources carrying capacity and the water temporal and water spatial evolution of water resources in the upper reaches of the Han River; ② on the whole, the water resources carrying capacity in the upper reaches of the Han River is excellent, and thanks to the continuous improvement of the local water use system, the water resources carrying capacity is increasing year by year. Although there are individual differences in different regions, they all have their own rising space, among which Hanzhong City has the best performance.